Molecular Mechanisms Elicited by d-Aspartate in Leydig Cells and Spermatogonia - Di Fiore, Maria Maddalena (Int J Mol Sci, 2016)
A bulk of evidence suggests that d-aspartate (d-Asp) regulates steroidogenesis and spermatogenesis in vertebrate testes. This review article focuses on intracellular signaling mechanisms elicited by d-Asp possibly via binding to the N-methyl-d-aspartate receptor (NMDAR) in both Leydig cells, and spermatogonia. In Leydig cells, the amino acid upregulates androgen production by eliciting the adenylate cyclase-cAMP and/or mitogen-activated protein kinase (MAPK) pathways. d-Asp treatment enhances gene and protein expression of enzymes involved in the steroidogenic cascade. d-Asp also directly affects spermatogonial mitotic activity. In spermatogonial GC-1 cells, d-Asp induces phosphorylation of MAPK and AKT serine-threonine kinase proteins, and stimulates expression of proliferating cell nuclear antigen (PCNA) and aurora kinase B (AURKB). Further stimulation of spermatogonial GC-1 cell proliferation might come from estradiol/estrogen receptor β (ESR2) interaction. d-Asp modulates androgen and estrogen levels as well as the expression of their receptors in the rat epididymis by acting on mRNA levels of Srd5a1 and Cyp19a1 enzymes, hence suggesting involvement in spermatozoa maturation.